2003
DOI: 10.1128/aac.47.11.3623-3626.2003
|View full text |Cite
|
Sign up to set email alerts
|

R57K Polymorphism in the Human Immunodeficiency Virus Type 1 Protease as Predictor of Early Virological Failure in a Cohort of Antiretroviral-Naive Patients Treated Mostly with a Nelfinavir-Containing Regimen

Abstract: In 243 antiretroviral-naive human immunodeficiency-infected patients starting a first-line-protease inhibitor (mainly nelfinavir)-containing therapy, the presence of the polymorphism R57K in the protease at the inception of therapy was independently associated with a higher rate of virological failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…These mutations have been shown to be associated with increased or decreased DR to some ARVs. 68–70 Several other mutations observed in this study were not classically associated with resistance and their biological functionality remains to be elucidated. Since some of the uncommon mutations occurred at a very high frequency in a subtype/CRF-specific manner, they may warrant further investigation to determine their biological functions within the virus genome.…”
Section: Discussionmentioning
confidence: 84%
“…These mutations have been shown to be associated with increased or decreased DR to some ARVs. 68–70 Several other mutations observed in this study were not classically associated with resistance and their biological functionality remains to be elucidated. Since some of the uncommon mutations occurred at a very high frequency in a subtype/CRF-specific manner, they may warrant further investigation to determine their biological functions within the virus genome.…”
Section: Discussionmentioning
confidence: 84%
“…At this position, amino‐acids AFIQST have also been found. R57K has been associated with a high rate of virological failure in patients prescribed regimens containing a PI (especially nelfinavir) [ 6]; this mutation was found in eight (13.1%) of 61 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Even though protease resistance patterns were not interpreted as conferring resistance by the rules‐based algorithm used, some minor mutations found at high prevalence, such as those at positions 10 or 36, have been associated with increased risk of virological failure [5]. Moreover, one study [6] has associated the presence of polymorphism R57K in the protease gene at baseline with early virological failure in anti‐retroviral‐naïve patients commencing first‐line therapy containing PIs (mainly nelfinavir), and this polymorphism was found in eight (13.1%) isolates from plasma in the present cohort. In some resistance positions listed by the IAS (positions 67, 75 and 215 in the RT gene, and positions 20, 36, 63 and 82 in the Pro gene), substitutions were found that are not considered by the IAS to be resistance‐related.…”
Section: Discussionmentioning
confidence: 99%
“…These insertions are positively correlated with PR codons associated with resistance to PIs whose usage has increased in recent years, including atazanavir (position 16) (38), lopinavir and amprenavir (position 47) (21,17), and tipranavir (positions 13, 36, and 47) (11). Additionally, a mutation at position 57 is a predictor of early virologic failure (23), and codon 91 mutations are more common in patients on long-term nonsupressive PI therapy (16). Mutations at position 11 are also associated with PI treatment (44,32).…”
Section: Discussionmentioning
confidence: 99%